0.5 V Fully Differential Universal Filter Based on Multiple Input OTAs - Winai Jaikla; Fabian Khateb; Montree Kumngern; Tomasz Kulej; Rajeev Kumar Ranjan; Peerawut Suwanjan (My University, 2020)
The design of a low-power, low-voltage, fully-differential universal biquad filter is presented in this work, which is constructed from four multiple-input gate-driven operational transconductance amplifiers (MI-OTAs) along with one passive resistor and two passive capacitors. The scheme of presented biquad filter has three high-input impedance voltage nodes and single output voltage node. Five unity gain filtering functions, all-pass (AP), low-pass (LP), band-pass (BP), high-pass (HP) and band-stop (BS) responses, are obtained. The selection of output filtering responses is obtained without the need of component matching condition, inverting or double input voltage. With this feature, it can be easily controlled with digital programming. The quality factor (Q) and angular frequency (ω 0 ) are electronically and independently tuned. Moreover, the adjustment of ω 0 and Q can be done without affecting the voltage gain. A workability of the design is confirmed via Cadence software and the Spectre simulator based on the 180 nm TSMC CMOS technology parameters. The proposed fully differential filter operates with 0.5 V supply voltage. The results verify that the proposed filter dissipates the total power of 53.3 nW. Additionally, the dynamic range (DR) of band-pass filtering function is 63 dB for 2% third intermodulation distortion (IMD). Also, the simulated RMS value of the band-pass filtering noise is 45μV.
Keywords: Digital biquad filter; Operational transconductance amplifier; Butterworth filter; Analog and Mixed-Signal Circuit Design